E-060 Utilisation of the Navien Distal Intracranial Catheter for Ultra-Distal Large-Bore Intracranial Access in the Treatment of Cerebrovascular Pathologies. (14th July 2013) - Lin, L; Colby, G; Huang, J; Tamargo, R; Coon, A
Abstract : Background: Successful neuroendovascular treatments rely on microcatheter stability from guide catheter support. We present our experience using a new large-bore, 0.058″ or 0.072″ inner diameter (ID), hyperflexible access catheter placed deep within the intracranial circulation during neurointervention. Methods: We retrospectively reviewed all neurointerventions performed by the senior author during an 18-month period to identify patients in whom the Navien intracranial catheter was placed in an ultra-distal position beyond the clinoidal internal carotid artery (ICA) or the V3 segment of the vertebral artery. Procedural data collected include parent artery tortuosity, technique for Navien advancement, final intra-procedural Navien position, and peri-procedural complications. Results: The Navien, either 6F 0.072" ID or 5F 0.058" ID, provided ultra-distal large-bore access in the following 11 intracranial interventions: anterior circulation aneurysm treatment with Pipeline embolisation device (PED), n=3; posterior circulation aneurysm single-stage stent-coiling, n=5; liquid embolisation of arteriovenous malformations, n=2; PED-coiling of posterior circulation aneurysm, n=1. Table 1 summarises the procedural data for these cases. The Navien was tracked into position over a Marksman microcatheter in 10/11 cases and a Headway 27 microcatheter in one case. Intra-procedural Navien positions were as follows: supraclinoid ICA, n=2; mid M1, n=1; V3–4 junction, n=2 (both using 6F Navien); distal V4, n=3; proximal basilar, n=1; proximal-mid basilar, n=1; mid basilar, n=1. No significant catheter-related complications occurred. Conclusion: The Navien catheter is the newest hyperflexible access catheter that is highly trackable into ultra distal intracranial positions. It manoeuvers atraumatically to provide improved distal intracranial support for a variety of complex cerebrovascular interventions and preserves necessary ID for quality intra-procedural roadmaps/angiography. Disclosures: L. Lin: None. G. Colby: None. J. Huang: None. R. Tamargo: None. A. Coon: 1; C; Stryker for SURPASS Trial and MicroVention for FRED Trial. 2; C; Covidien. 6; C; Pipeline Proctor.